The effect of the morphology of Chlef on the quality of the public transport servive - Rassi, Houssam; Benmissi, Ahcene (Journal of Human Sciences, 2021)
Algeria has witnessed a development in the modernization of the transport sector through the various projects that have been achieved in the various Wilayas. The city of Chlef, with an area of ​​112 km², a population of 220,000 in 2020, and despite its strategic location and possession of qualifications that would help it to be a metropolitan city, it still suffers from transportation problems through its various neighborhoods, especially in the city center. This study aimed to analyze the quality of public transport service and its relationship with the morphology of the city and its urban development., By using the most important approaches on the analytical descriptive, especially on applied study By taking direct notes. We also distributed questionnaire forms and conducted interviews with officials in various departments Finally, we concluded proposing some solutions for the development of transportation and solving the problem of traffic congestion.